WadD, a New Brucella Lipopolysaccharide Core Glycosyltransferase Identified by Genomic Search and Phenotypic Characterization - Salvador-Bescós, Miriam; Gil-Ramírez, Yolanda; Zúñiga-Ripa, Amaia; Martínez-Gómez, Estrella; de Miguel, María J.; Muñoz, Pilar M.; Cloeckaert, Axel; Zygmunt, Michel S.; Moriyón, Ignacio; Iriarte, Maite; Conde-Álvarez, Raquel (Frontiers in Microbiology, 2018)
Brucellosis, an infectious disease caused by Brucella, is one of the most extended bacterial zoonosis in the world and an important cause of economic losses and human suffering. The lipopolysaccharide (LPS) of Brucella plays a major role in virulence as it impairs normal recognition by the innate immune system and delays the immune response. The LPS core is a branched structure involved in resistance to complement and polycationic peptides, and mutants in glycosyltransferases required for the synthesis of the lateral branch not linked to the O-polysaccharide (O-PS) are attenuated and have been proposed as vaccine candidates. For this reason, the complete understanding of the genes involved in the synthesis of this LPS section is of particular interest. The chemical structure of the Brucella LPS core suggests that, in addition to the already identified WadB and WadC glycosyltransferases, others could be implicated in the synthesis of this lateral branch. To clarify this point, we identified and constructed mutants in 11 ORFs encoding putative glycosyltransferases in B. abortus. Four of these ORFs, regulated by the virulence regulator MucR (involved in LPS synthesis) or the BvrR/BvrS system (implicated in the synthesis of surface components), were not required for the synthesis of a complete LPS neither for virulence or interaction with polycationic peptides and/or complement. Among the other seven ORFs, six seemed not to be required for the synthesis of the core LPS since the corresponding mutants kept the O-PS and reacted as the wild type with polyclonal sera. Interestingly, mutant in ORF BAB1_0953 (renamed wadD) lost reactivity against antibodies that recognize the core section while kept the O-PS. This suggests that WadD is a new glycosyltransferase adding one or more sugars to the core lateral branch. WadD mutants were more sensitive than the parental strain to components of the innate immune system and played a role in chronic stages of infection. These results corroborate and extend previous work indicating that the Brucella LPS core is a branched structure that constitutes a steric impairment preventing the elements of the innate immune system to fight against Brucella.